(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the linguistic and cultural features of phrases and expressions related to the concept “school” in English and Uzbek languages. The research focuses on semantic, structural, and cultural aspects of how school is conceptualized and verbalized in both linguistic systems. The results show that while English phrases emphasize individual experience, discipline, and lifelong learning, Uzbek expressions reflect moral education, respect for teachers, and social harmony. The study reveals that the concept of school functions as a key linguistic and cultural symbol in shaping both intellectual and moral development.